Explaining Employee Performance in Indonesia: The Role of Leadership, Work Environment, and Communication - Komarun Zaman; Priyo Utomo (International Journal of Economics, Science, and Education, 2025)
Purpose:This study aims to investigate the effects of leadership style, work environment, and communication style on employee performance and morale in Digital Small and Medium-sized Enterprises (SMEs) in Indonesia, as well as to examine the mediating role of job performance in shaping employee morale. Design/methodology/approach: This study adopts a quantitative research design using hypothesis testing. Data were collected through a survey of employees working in Digital SMEs in Indonesia and analyzed using Statistical Package for the Social Sciences (SPSS). The relationships among leadership style, work environment, communication style, employee performance, and employee morale were examined using regression-based statistical analysis. Findings: The results indicate that leadership style, work environment, and communication style have significant positive effects on employee performance and morale. Leadership style emerges as a key determinant, with effective leadership enhancing both employee morale and performance. A supportive work environment improves employee morale and indirectly strengthens performance through job satisfaction. Furthermore, effective communication styles positively influence employee morale and performance. The findings also confirm that job performance mediates the relationship between leadership style, work environment, communication style, and employee morale. Research limitations/implications: This study is limited to Digital SMEs in Indonesia and relies on cross-sectional survey data, which may restrict the generalizability of the results. Future studies are encouraged to apply longitudinal designs, involve larger and more diverse samples, and incorporate additional organizational variables to enrich the analysis. Practical implications:The findings provide practical guidance for leaders and managers of Digital SMEs in designing effective leadership practices, creating supportive work environments, and implementing clear communication strategies to enhance employee morale and performance in digital business settings. Originality/value:This study offers empirical evidence on the interplay between leadership style, work environment, and communication style in influencing employee performance and morale within the context of Digital SMEs in Indonesia, highlighting the mediating role of job performance. Paper type:Empirical research.